Housing: Who Decides? - King, P. author. aut Link
VI, 193 p.
Keywords: Housing: Who Decides ? consists of a debate between a political theorist and an economist on decision-making in housing. Each author develops a normative argument linking theoretical and policy analyses to establish the abilities of the state and individuals to determine housing outcomes.